Servant Leadership Competence to Improve the Quality of Services for Health Workers Graduates of the Akademi Kesehatan John Paul II Pekanbaru - Anna Maria (Jurnal Pengabdian Masyarakat Bestari, 2023)
Leadership is a person's ability to influence others. Leadership competency is required in doing work. Servant leadership is one of the competencies that medical laboratory technologies must possess in serving laboratory visitors. Therefore, this service chose "Servant Leadership Competence to Improve the Quality of Services for Health Workers Graduates of the Akademi Kesehatan John Paul II Pekanbaru". The method of this activity is a seminar - interactive dialogue – face-to-face group discussion with 32 participants. The purpose of this activity is for participants to master the concept of serving leadership, form a commitment to serve and manifest serving behaviour to participants as medical laboratory technologies. Technologies who apply the service will create comfort and satisfaction for laboratory visitors, impacting the increasing number of laboratory visitors.